Analisis Capability UMKM Teh Tubruk Dalam Menyesuaikan Diri Terhadap Tren Minuman Kekinian Di Lingkungan Kampus UIN Raden Intan Lampung - Ella Hayati; Nadira Isaura Prameswari; Vicky F Sanjaya (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to examine how the Teh Tubruk micro-enterprise develops dynamic capabilities to adapt to contemporary beverage trends within the UIN Raden Intan Lampung campus area. The research applies a descriptive qualitative method, with data obtained through in-depth interviews and direct observation of the business owner. The results indicate that sensing capability emerges from the owner’s efforts to monitor shifts in student preferences and keep track of popular beverage trends. The seizing capability is reflected in product innovations, price adjustments, and simple promotional strategies designed to attract campus consumers. Meanwhile, transforming capability is demonstrated through improvements in production procedures, more efficient raw material management, and ongoing operational adjustments to sustain the business amid increasing competition from modern beverage products. This study concludes that the integration of these three capabilities plays a vital role in supporting the resilience of Teh Tubruk. The findings contribute to the theoretical understanding of dynamic capability within traditional micro-enterprises and provide practical implications regarding the need for market awareness, innovation flexibility, and adaptive resource management among small businesses.